Oxidation of nonylphenol ethoxylates in aqueous solution by UV-C photolysis, H2O2/UV-C, Fenton and photo-Fenton processes: are these processes toxicologically safe? - Karci, Akin; Arslan-Alaton, Idil; Bekbolet, Miray (IWA Publishing, 2013)
UV-C, H2O2/UV-C, Fenton and photo-Fenton treatment of a nonylphenol polyethoxylate (NP-10) were comparatively studied, primarily focusing on the acute toxicity of degradation products. Formic, acetic and oxalic acids were all identified as the degradation products of NP-10; however, the sole common carboxylic acid was found to be formic acid for the studied treatment processes. The percent relative inhibition towards Vibrio fischeri increased from 9% to 33% and 24% after 120 min-UV-C and H2O2/UV-C treatment, respectively. Complete NP-10 and 70% of its total organic carbon (TOC) content was removed by the photo-Fenton process, which ensured the fastest removal rates and lowest inhibitory effect (8% after 120 min treatment). The acute toxicity pattern being observed during H2O2/UV-C and photo-Fenton treatment positively correlated with temporal evolution of the identified carboxylic acids, whereas unidentified oxidation products were the most likely origin of the acute toxicity in UV-C photolysis.
Keywords: Photolysis; Photochemistry; Ultraviolet Rays; Carboxylic Acids; Hydrogen Peroxide; Aliivibrio fischeri; Polyethylene Glycols; Solutions; Toxicity Tests, Acute; Oxidation-Reduction; Water Pollutants, Chemical